ANALISIS PERAN AUDIT INTERNAL TERHADAP PENGENDALIAN INTERN PENERIMAAN KAS ( STUDI KASUS PADA PT HARAPAN PANCA SUKMA ) - Oktaria, Eka Travilta; Astuti, Dwi; Sari, Pipit Novila (Universitas Teknokrat Indonesia, 2023)
This study aims to determine the role of internal audit on internal control of cash receipts at PT Harapan Pamca Sukma whether it is running well. The type of research method used is descriptive qualitative research method. Cash is the most liquid current asset and cash plays an important role in influencing the smooth operation of the company. Efforts to improve cash control in the company are through the implementation of internal audits of cash, which will support the effectiveness of internal cash control. Based on the research results obtained from PT Harapan Panca Sukma, it can be seen that the role of internal audit on internal control of cash receipts at PT Harapan Panca Sukma has been carried out in accordance with the COSO method procedure, where all existing components have been implemented properly and adequately. So far, the auditors at PT Harapan Panca Sukma have carried out their duties and responsibilities properly in accordance with the policies that have been determined.